(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2022)
The article deals with main aspects of actualization of semantics of quantity in modern Ukrainian, English, and Russian culinary recipes. The language means of expression of quantitativeness are described. The semantics of quantity is a necessary component of a recipe text. Quantitative relations are manifested in different semantic planes of the analyzed texts: according to substance and objects, actions, temporality. Quantitativeness is a necessary component of structural-semantic part of the recipe text “list of ingredients”. The descriptive-instructive part of the recipe can emphasize not only the number of certain components of the dish, but their spatial size, divisibility. Quantitative parameters are indicated for the duration of a certain action (state), as well as for the general quantitative characteristics of the time required for cooking. Temperature parameters of cooking are described with quantitative characteristics. The meaning of the definite and indefinite quantity is expressed in the texts of culinary recipes. Noun phrases with pre-modifying numerals are the main language means of expression of quantitativeness. The usage of measuratives, and other words meaning “unit of measure” is typical. Means and ways of expression of quantitativeness have national-cultural specificity.